Clinical Delivery and Effectiveness of Music Therapy in Hematology and Oncology: An EMMPIRE Retrospective Study. (December 2022) - Rodgers-Melnick, Samuel N.; Rivard, Rachael L.; Block, Seneca; Dusek, Jeffery A.
Background: Music therapy (MT) has been shown to improve outcomes for patients with sickle cell disease (SCD) and patients with hematologic and/or oncologic conditions excluding SCD (HemOnc) in prior randomized trials. While few studies have described the clinical delivery (ie, volume, clinical settings, patient characteristics, referrals, and session characteristics) of MT and examined its real-world effectiveness, no studies have compared responses between hematology/oncology populations. The purpose of this study was to examine the clinical delivery and effectiveness of MT at a freestanding academic cancer center and compare the effectiveness of MT on pain, anxiety, and fatigue between adult patients in the HemOnc and SCD groups. Methods: A retrospective review was conducted of all MT sessions provided at a freestanding academic cancer center between January 2017 and July 2020. The unadjusted single-session effects of MT on pain, anxiety, and fatigue were assessed among patients reporting symptoms ≥1 out of 10 on a 0 to 10 scale. Adjustments were made for multiple sessions on the same patient using a mixed model to compare pre-session and change scores between the HemOnc and SCD groups. Patients' comments were analyzed using conventional qualitative content analysis. Results: Music therapists provided 4002 sessions to 1152 patients including 1012 in the HemOnc group and 140 in the SCD group. In the combined sample, statistically significant reductions in pain (1.48 units), anxiety (2.58 units), and fatigue (0.84 units) were observed, with changes in pain and anxiety exceeding clinically significant thresholds. After adjustment, the SCD group reported significantly greater pre-session pain (7.22 vs 5.81) and anxiety (6.11 vs 5.17) as well as greater anxiety reduction (2.89 vs 2.23) than the HemOnc group. Patients' comments contained themes including enjoyment, gratitude, and improvements in mood, pain, and anxiety. Conclusions: This study supports the delivery and clinical effectiveness of MT for addressing the needs of patients throughout their course of treatment at an academic cancer center and justifies the inclusion of individuals with SCD within integrative oncology services.